Pengaruh Employer Branding Berbasis Development Value terhadap Loyalitas Karyawan pada Coca-Cola Official Distribution Bandung - Pernanda, Teguh Satrio; Sri Suwarsi; Indra Fajar Alamsyah (Bandung Conference Series: Business and Management, 2023)
Abstract. Employer branding based on development values plays a very important role in building employee loyalty. This is because employees tend to respond positively to companies that show a commitment to developing their potential and helping them develop professionally. This study aims to analyze the effect of developing value-based employee branding on employee loyalty at Coca-Cola Official Distribution. Coca-Cola Authorized Distribution is an authorized distribution company operating within the Coca-Cola product supply chain. This study uses a quantitative approach using a questionnaire as a data collection instrument. The research sample consisted of employees working in the sales department of Coca-Cola Official Distribution. The focus of the research is the influence of Employer Branding applied by companies that are oriented towards developing employee values. The results of this study indicate that employee branding based on developmental values at Coca-Cola Official Distribution has been running well and effectively in several ways that the company has done to make employees feel more comfortable while working at the company. The results of this study also indicate that employee loyalty to Coca-Cola Official Distribution can be categorized as quite good, as evidenced by the presence of employees who have long devoted themselves to the company and continue to try to help the company achieve its goals or targets. This study also found that development value-based employee branding components, such as clear development opportunities, relevant training programs, effective mentoring, and structured career paths, have a significant influence on the level of employee loyalty at Coca-Cola Official Distribution. The practical implication of this study is the importance of Coca-Cola Authorized Distribution companies in implementing an effective development value-based employee branding strategy. By paying serious attention to developing employee values, companies can increase employee loyalty and motivate them to continue to make positive contributions in the long term. Abstrak. Employer branding berbasis development value memainkan peran yang sangat penting dalam membangun loyalitas karyawan. Ini karena karyawan cenderung merespons positif terhadap perusahaan yang menunjukkan komitmen dalam mengembangkan potensi mereka dan membantu mereka tumbuh secara profesional. Penelitian ini bertujuan untuk menganalisis pengaruh employer branding berbasis development value terhadap loyalitas karyawan di Coca-Cola Official Distribution. Coca-Cola Official Distribution merupakan perusahaan distribusi resmi yang beroperasi dalam rantai pasokan produk Coca-Cola. Penelitian ini menggunakan pendekatan kuantitatif dengan menggunakan kuesioner sebagai instrumen pengumpulan data. Sampel penelitian terdiri dari karyawan yang bekerja di departemen sales di Coca-Cola Official Distribution. Fokus penelitian adalah pada pengaruh employer branding yang diterapkan oleh perusahaan yang berorientasi pada pengembangan nilai karyawan. Hasil penelitian ini menunjukan bahwa employer branding berbasis development value di Coca-Cola Official Distribution sudah berjalan dengan baik dan efektif dengan beberapa cara yang telah di lakukan perusahaan untuk membuat karyawan merasa lebih nyaman ketika bekerja di perusahaan. Hasil penelitian ini juga menunjukan bahwa loyalitas karyawan di Coca-Cola Official Distribution dapat dikategorikan cukup baik, terbukti dengan adanya karyawan yang sudah lama mendedikasikan dirinya terhadap perusahaan dan terus berusaha membantu perusahaan dalam mencapai tujuan atau target perusahan. Penelitian ini juga menemukan bahwa komponen-komponen employer branding berbasis development value, seperti kesempatan pengembangan yang jelas, program pelatihan yang relevan, pendampingan yang efektif, dan jenjang karir yang terstruktur, memiliki pengaruh yang signifikan terhadap tingkat loyalitas karyawan di Coca-Cola Official Distribution. Implikasi praktis dari penelitian ini adalah pentingnya perusahaan Coca-Cola Official Distribution dalam menerapkan strategi employer branding berbasis development value yang efektif. Dengan memberikan perhatian yang serius pada pengembangan nilai karyawan, perusahaan dapat meningkatkan loyalitas karyawan dan memotivasi mereka untuk tetap berkontribusi secara positif dalam jangka panjang.